Operating Voltage and Frequency Regime Validation of Grid Code Requirements in South Africa - Gideon D. Joubert; Atanda K. Raji (International Transactions on Electrical Energy Systems)
South Africa first implemented rolling blackouts known as load shedding to protect the integrity and maintain stability of their ailing electrical grid over a decade ago. Since then, load shedding has become a daily occurrence, which South Africa plans to alleviate through the addition of grid-connected renewable generation. Significant renewable energy (RE) additions can however negatively affect a grid, prompting South Africa to develop RE-specific grid code requirements as mitigation. Given this strategy to address the country’s supply challenges using RE, and the still unknown effects of the country’s aggressive RE integration planned, South Africa must perform the necessary simulations tailored to the country’s unique grid conditions, and local RE-specific grid code requirements to ensure a RE-driven solution are indeed viable. Prompted by the lack of a suitably tailorable simulation platform, this paper proceeds to discuss the development of a tailorable grid code-guided renewable power plant (RPP) behavioral studies testbed. The testing methodology involves feeding grid disturbance event data to an RPP modeled after Eskom’s Sere wind farm in South Africa, which is operated in line with local RPP-specific grid code voltage and frequency requirements to assess the testbed’s grid code-guided RPP operating approach. Results show the testbed to effectively distinguish between grid code-specified no-fault, fault ride-through, and trip conditions, operating the simulated RPP accordingly. Consequently, as compared to comparable RE integration simulation platforms, the reviewed testbed has the potential of producing individualized results, owing to its tailorable grid, RPP, and incorporated grid code guiding specifications.